Modelling of all optical switch based on Symmetric Mach-Zehnder (SMZ) using symmetric and asymmetric coupler: article / Ahmad Faizal Yahya - Yahya, Ahmad Faizal
As increasing capacity demand in telecommunication system, the ultrahigh-speed optical network was developing rapidly. In these networks, it is important to the switching, routing and processing in optical domain to prevent bottlenecks of optoelectronic conversions. Using all optical switches based on Symmetric Mach-Zehnder (SMZ), characteristics and switching window profile was investigated in this paper. As compared to the various interferometer based switch configurations, the SMZ structure provides the most flexibility, compact size, low power operation, shortest switching window and thermal stability. This paper presents the modelling based on SMZ switch. The analysis of conventional and proposed SMZ switch by using symmetric coupler (50:50 couplers) and asymmetric coupler (60:40 couplers) placed at the end of this switch was shown and compared. The performance and advantages of these proposed SMZ switch coupler are also analyzed.